MDS evidence‐based review of treatments for essential tremor. Issue 7 (2nd May 2019) - Ferreira, Joaquim J.; Mestre, Tiago A.; Lyons, Kelly E.; Benito‐León, Julián; Tan, Eng‐King; Abbruzzese, Giovanni; Hallett, Mark; Haubenberger, Dietrich; Elble, Rodger; Deuschl, Günther; ,
Abstract: Background: Essential tremor is one of the most prevalent movement disorders. Many treatments for essential tremor have been reported in clinical practice, but it is uncertain which options have the most robust evidence. The International Parkinson and Movement Disorder Society commissioned a task force on tremor to review clinical studies of treatments for essential tremor. Objectives: To conduct an evidence‐based review of current pharmacological and surgical treatments for essential tremor, using standardized criteria defined a priori by the International Parkinson and Movement Disorder Society. Methods: We followed the recommendations of the International Parkinson and Movement Disorder Society Evidence Based Medicine Committee. Results: Sixty‐four studies of pharmacological and surgical interventions were included in the review. Propranolol and primidone were classified as clinically useful, similar to Topiramate, but only for doses higher than 200 mg/day. Alprazolam and botulinum toxin type A were classified as possibly useful . Unilateral Ventralis intermedius thalamic DBS, radiofrequency thalamotomy, and MRI‐guided focused ultrasound thalamotomy were considered possibly useful . All the above recommendations were made for limb tremor in essential tremor. There was insufficient evidence for voice and head tremor as well as for the remaining interventions. Conclusion: Propranolol, primidone, and topiramate (>200 mg/day) are the pharmacological interventions in which the data reviewed robustly supported efficacy. Their safety profile and patient preference may guide the prioritization of these interventions in clinical practice. MRI‐guided focused ultrasound thalamotomy was, for the first time, assessed and was considered to be possibly useful . There is a need to improve study design in essential tremor and overcome the limitation of small sample sizes, cross‐over studies, short‐term follow‐up studies, and use of nonvalidated clinical scales. © 2019 International Parkinson and Movement Disorder Society